Solutions Manual for Techniques of Problem Solving - Fernandez, Luis ; Gooransarab, Haedeh (Universities Press ( India ) Limited, 1998)
A companion to ""Techniques of Problem Solving"", this Solutions Manual addresses most end-of-chapter exercises in the book proper.